Multigroup Ethnic Identity Measure: factorial structrure in Ukrainian immigrants in western Europe - Frias-Navarro, Dolores; Botvyn, Yanina; Pascual-Soler, Marcos; Berrios-Riquelme., Jose (Opción, 1970)
The objective of this study is to evaluate the factorial structure of the Multigroup EthnicIdentity Measure on Ukrainians immigrants in two countries of Occidental Europe. Thefactorial structure was put to test with a confirmatory factorial analysis and with the factorialinvariance between the samples of both countries. The results indicate that the twodimensionalstructure has a better adjustment than the one-dimensional, two dimensions havea good internal consistency and they are directly correlated. The factorial invariance betweenboth countries has also been proved. It is concluded that the measure presents a twodimensionstructure and suggestions for future investigations are proposed.